Bioactive-hybrid-zirconia implant surface for enhancing osseointegration: an in vivo study - Dawlat Mostafa; Moustafa Aboushelib (SpringerOpen, 2018)
Abstract Background Zirconia is characterized by a hard, dense, and chemically inert surface which requires additional surface treatments in order to enhance osseointegration. The proposed hypothesis of the study was that combination of a nano-porous surface infiltrated with a bioactive material may enhance osseointegration of zirconia implants. Methods Custom-made zirconia implants (3.7 mm × 8 mm) were designed, milled, and sintered according to manufacturer recommendations. All implants received selective infiltration etching (SIE) technique to produce a nano-porous surface. Surface porosities were either filled with nano-hydroxy apatite particle- or platelet-rich plasma while uncoated surface served as a control (n = 12, α = 0.05). New surface properties were characterized with mercury porosimetry, XRD analysis, SEM, and EDX analysis. Implants were inserted in femur head of rabbits, and histomorphometric analysis was conducted after healing time to evaluate bone-implant contact percentage (BIC%). Results Selective infiltration etching produced a nano-porous surface with interconnected surface porosities. Mercury porosimetry revealed a significant reduction in total porosity percent after application of the two coating materials. XRD patterns detected hexagonal crystal structure of HA superimposed on the tetragonal crystal phase of zirconia. Histomorphometric analysis indicated a significantly higher (F = 14.6, P < 0.001) BIC% around HA-bioactive-hybrid surface (79.8 ± 3%) and PRP-coated surface (71 ± 6 %) compared to the control (49 ± 8%). Conclusions Bioactive-hybrid-zirconia implant surface enhanced osseointegration of zirconia implants.